Prioritising CVD prevention therapy - absolute risk versus individual risk factors. - Doust, J; Sanders, S; Shaw, J; Glasziou, P (2012)
BACKGROUND: Previous studies suggest that a high proportion of persons at high risk of cardiovascular disease in Australia are not receiving adequate disease prevention with blood pressure and lipid lowering therapy. However, it is not clear how a move to an absolute risk factor approach will affect the proportion of the population that is treated with blood pressure and lipid lowering therapy versus treatment based on individual risk factors. METHODS: We classified participants in the AusDiab follow up cohort study who had no previous history of cardiovascular disease and who were not taking blood pressure or lipid lowering medication currently according to the presence of individual risk factors versus combined absolute risk. RESULTS: Of the 3627 participants who were untreated, 429 (12%) had elevated blood pressure and 983 (27%) had dyslipidaemia, with 167 (5%) having both risk factors. 1245 participants (34%) would be treated using the individual risk factor approaches and 281 (8%) using the absolute risk approach based on the most clearly defined criteria of high risk. CONCLUSION: Moving to an absolute risk approach prioritises treatment to those most at risk, but ambiguities regarding what is meant by the absolute risk approach remain.